Students' and Teachers' Perceptions of Moral-Spiritual Values in Ta'lim Muta'allim: A Qualitative Study in Pesantren and Non-Pesantren Schools - Zilva Raihan Nazir Ali Alfathimy; Udin Supriadi; Syahidin Syahidin; Cucu Surahman (Sakura Digital Nusantara, 2026)
Purpose This study aims to examine the moral-spiritual values embedded in the book Ta'lim Muta'allim and their relevance in addressing the crisis of students' courtesy towards teachers in the contemporary era. Methods This research employs a qualitative approach. The primary data source is the book Ta'lim Muta'allim, analyzed through the perspective of moral and spiritual education. Secondary data were acquired through in-depth interviews with high school teachers and students to explore their perceptions regarding students' moral-spiritual attitudes toward teachers. Findings The results indicate that students possess a highly positive perception of the moral-spiritual values derived from the book Ta’lim Muta’allim. Similarly, teachers also demonstrated a high perception regarding these values. Research Implications Integrating the teachings of Ta'lim Muta'allim into the modern educational system, specifically within moral-spiritual education, can serve as a viable solution to overcome the moral crisis among students. This study recommends implementing the moral-spiritual values from Ta'lim Muta'allim as an integral component of the character-based education curriculum in schools to strengthen students' moral and spiritual attitudes towards their teachers. Originality The decline in students' respect and courtesy towards teachers in the modern era has emerged as a serious issue within the educational sphere. Cultural shifts driven by digital technological advancements have displaced moral-spiritual values, particularly concerning student-teacher interactions. The book Ta'lim Muta'allim by Sheikh Az-Zarnuji offers a relevant solution through its moral and spiritual teachings on the pursuit of knowledge.